Предмет: Алгебра,
автор: pashagrek5
(c+3)(a-4) помогите пожалуйста
Ответы
Автор ответа:
0
Полный Ответ:
Ответ:
Объяснение:
Перемножаем скобки и упрощаем выражение (переносим -4c и +3a).
Автор ответа:
0
Ответ:ac+3a-4c-12
Объяснение:
(c+3)-(a-4)=c(a-4)+3(a-4)=ac-4+3(a-4)=ac-4c+3a-12=ac+3a-c4c-12=ac+3a-4c-12
Похожие вопросы
Предмет: История,
автор: 3DIKS
Предмет: Психология,
автор: mikkkan
Предмет: Алгебра,
автор: manevichtana
Предмет: История,
автор: 31danika08
Предмет: Русский язык,
автор: psoldatov